PENGARUH KEPEMIMPINAN DAN PENERAPAN MODEL ABSENSI FINGERPRINT TERHADAP PRODUKTIVITAS KERJA DENGAN DISIPLIN KERJA SEBAGAI VARIABEL MODERATING - Netty Laura (Business Management Journal, 2019)
ABSTRACTThis study aims to analyze the influence of Leadership and Application of Fingerprint Attendance Model to Work Productivity With Work Discipline as Moderating Variable. In this research,  sampling method used is accidental sampling method (non-probability sampling). In this study using three variables, independent variables are Leadership (X1) and Attendance Model Fingerprint (X2) with dependent variable is Productivity (Y) and moderating variable is Discipline (Z). Population in this research is employees at PT. ASTRA Daihatsu Motor, and samples are 85 respondents. The result of the research shows that Leadership variable is not able to moderate to Work Productivity, Fingerprint Attendance Model variable has a significant effect on Work Productivity, Work Discipline variable also has a significant effect on Work Productivity, Leadership and Work Discipline is not able to moderate to Work Productivity, Fingerprint and Discipline Attendance Model Work is also not able to moderate against Work ProductivityKeywords: Leadership, Fingerprint Attendance Model, Work Productivity, and Work Discipline.